Oral administration of carvacrol/β-cyclodextrin complex protects against 6-hydroxydopamine-induced dopaminergic denervation. (June 2019) - Tiefensee Ribeiro, Camila; Gasparotto, Juciano; Petiz, Lyvia Lintzmaier; Brum, Pedro Ozorio; Peixoto, Daniel Oppermann; Kunzler, Alice; da Rosa Silva, Helen Tais; Bortolin, Rafael Calixto; Almeida, Roberto Farina; Quintans-Junior, Lucindo José; Araújo, Adriano Antunes; Moreira, José Claudio Fonseca; et al.
Abstract: Carvacrol (CARV) presents valuable biological properties such as anti-inflammatory and antioxidant activities. However, pharmacological uses of CARV are largely limited due to disadvantages related to solubility, bioavailability, preparation and storage processes. The complexation of monoterpenes with β-cyclodextrin (β-CD) increases their stability, solubility and oral bioavailability. Here, the protective effect of oral treatment with CARV/β-CD complex (25 μg/kg/day) against dopaminergic (DA) denervation induced by unilateral intranigral injection of 6-hydroxydopamine (6-OHDA - 10 μg per rat) was analyzed, in order to evaluate a putative application in the development of neuroprotective therapies for Parkinson's disease (PD). Pretreatment with CARV/β-CD for 15 days prevented the loss of DA neurons induced by 6-OHDA in adult Wistar rats. This effect may occur through CARV anti-inflammatory and antioxidant properties, as the pretreatment with CARV/β-CD inhibited the release of IL-1β and TNF-α; besides, CARV prevented the increase of mitochondrial superoxide production induced by 6-OHDA in cultured SH-SY5Y cells. Importantly, hepatotoxicity or alterations in blood cell profile were not observed with oral administration of CARV/β-CD. Therefore, this study showed a potential pharmacological application of CARV/β-CD in PD using a non-invasive route of drug delivery, i.e., oral administration. Highlights: CARV/β-CD prevented the loss of DA neurons. CARV/β-CD decreased the release of inflammatory mediators in CSF and serum. CARV reduced the mitochondrial production of superoxide induced by 6-OHDA. CARV/β-CD did not induce systemic toxicity.